Understanding inter‐generational relations: the case of health maintenance by children. Issue 2 (6th February 2015) - Mayall, Berry
Abstract This paper aims to consider the sociology of childhood in relation to child health maintenance, restoration and promotion, through discussion of three intersecting themes: children as a minority social group; children as embodied social actors and children as agents in the inter‐generational division of labour. I build on my previous work on children's negotiations of their health status, at home and at school and review some important developments and research studies over the last 15 years or so. This period has seen the expansion of research on childhood, linguistically and geographically; and has focused attention on how children's health and well‐being relate to social expectations of them as paid workers and as schoolchildren.